Glycan involvement in the adhesion of Pseudomonas aeruginosa to tears. (April 2016) - Kautto, Liisa; Nguyen-Khuong, Terry; Everest-Dass, Arun; Leong, Andrea; Zhao, Zhenjun; Willcox, Mark D.P.; Packer, Nicolle H.; Peterson, Robyn
Abstract: The human eye is constantly bathed by tears, which protect the ocular surface via a variety of mechanisms. The O -linked glycans of tear mucins have long been considered to play a role in binding to pathogens and facilitating their removal in the tear flow. Other conjugated glycans in tears could similarly contribute to pathogen binding and removal but have received less attention. In the work presented here we assessed the contribution of glycan moieties, in particular the protein attached N -glycans, presented by the broad complement of tear proteins to the adhesion of the opportunistic pathogen Pseudomonas aeruginosa, a leading cause of microbial keratitis and ulceration of the cornea. Our adhesion assay involved immobilising the macromolecular components of tears into the wells of a polyvinyl difluoride (PVDF) microtitre filter plate and probing the binding of fluorescently labelled bacteria. Three P. aeruginosa strains were studied: a cytotoxic strain (6206) and an invasive strain (6294) from eye infections, and an invasive strain (320) from a urinary tract infection (UTI). The ocular isolates adhered two to three times more to human tears than to human saliva or porcine gastric mucin, suggesting ocular niche-specific adaptation. Support for the role of the N -glycans carried by human tear proteins in the binding and removal of P. aeruginosa from the eye was shown by: 1) pre-incubation of the bacteria with free component sugars, galactose, mannose, fucose and sialyl lactose (or combination thereof) inhibiting adhesion of all the P. aeruginosa strains to the immobilised tear proteins, with the greatest inhibition of binding of the ocular cytotoxic 6206 and least for the invasive 6294 strain; 2) pre-incubation of the bacteria with N -glycans released from the commercially available human milk lactoferrin, an abundant protein that carries N -linked glycans in tears, inhibiting the adhesion to tears of the ocular bacteria by up to 70%, which was significantly more binding inhibition than by the same amount of intact human lactoferrin or by the plant-derived N -glycans released from the rice recombinant lactoferrin; 3) pre-incubation of the bacteria with N-linked glycans released from human tear proteins inhibiting the adhesion of the ocular P. aeruginosa strains to immobilised tear proteins; 4) inhibition by the N -glycans from lactoferrin of the ability of an ocular strain of P. aeruginosa to invade corneal epithelial cells; 5) removal of terminal sialic acid and fucose moieties from the tear glycoproteins with α2-3, 6, 8 neuraminidase (sialidase) and α1-2, 3, 4 fucosidase resulting in a reduction in binding of the UTI P. aeruginosa isolate, but not the adhesion of the ocular cytotoxic (6206) or invasive (6294) isolates. Glycosidase activity was validated by mass spectrometry. In all cases, the magnitude of inhibition of bacterial adhesion by the N -glycans was consistently greater for the cytotoxic ocular strain than for the invasive ocular strain. Ocular P. aeruginosa isolates seems to exhibit different adhesion mechanism than previously known PAI and PAII lectin adhesion. The work may contribute towards the development of glycan-focused therapies to prevent P. aeruginosa infection of the eye. Graphical abstract: Highlights: Protein linked N -glycans are involved in adhesion of the pathogen Pseudomonas aeruginosa to tears. Lactoferrin, human tear N -linked glycans and free sugars inhibit P. aeruginosa adhesion. Strains of P. aeruginosa differ in their dependence on specific glycans for tear adhesion. N -glycans from lactoferrin inhibit invasion of an ocular isolate of P. aeruginosa . Potential for glycan-focused therapies to prevent ocular P. aeruginosa infection.